Dental Management of Patient With Von Willebrand Disease - V, Ambarkova; A, Jovanovska; J, Ambarkov (Archives of Clinical and Medical Case Reports, 2019)
Von Willebrand disease is a lifelong bleeding disorder in which your blood doesn't clot well. Some people may suspect they have a bleeding disorder when they have heavy bleeding after a dental procedure. Mutations in the von Willebrand disease gene cause von Willebrand disease. The von Willebrand factor as a blood clotting protein was provided by the VWF gene and is essential for the formation of blood clots. Methods: Ten year old boy come with his mother to the Department for preventive and pediatric dentistry, University Dental Clinic Centar St Pantelejmon- Skopje. During a visit to the pediatric dental clinic, the need for extraction of several primary teeth was detected with a clinical and rtg examination. The child has already made blood test and results showed a borderline of vWF Ris Co and vWF Ag and hypoagreligidity of the Tr. Timely boy complains of chest pain and also has a chronic eczema. The child is monitored in a hematologic ambulance due to the vWF Ag boundary level and hypoaggregability of Tr. For haemostasis after the extraction of a primary tooth, local application of amp.Tranexamic acid and fibrin foam is recommended by his heamatologist. Conclusion: For successful extraction of the primary teeth in patient with von Willebrand disease consultation with a haematologist is necessary.